Design of iris mechanism for flexion and extension training in hand rehabilitation - Ali, Muhammad Aminuddin Anwar; Zainul Azlan, Norsinnira (Asian Research Publishing Network (ARPN), 2016)
Rehabilitation therapy is the process to reduce the impairments and disabilities of upper or lower limb that are caused by accidents or stroke. This paper presents the design and development of a new hand rehabilitation device based on iris mechanism with basic Arduino coding to train the flexion and extension of the hand. The iris mechanism is designed using SolidWorks 2015 and the prototype is developed using ABS filament and perspex. The steps to design the iris mechanism is shown in this paper, starting with the first layer (lower body), then the blade, second layer with gear, and third layer (for holding all layers together). The measurement of inside diameter is decided by considering the average size of object can hold by the patient for basic daily life. The inside diameter of the iris mechanism varies from 15 mm to 110 mm to enable the patients to adapt to various object sizes. The device can be used for the right-handed or left-handed person. The preliminary output shows that the designed mechanism is able to perform the opening and closing motion for the rehabilitation of hand function. The holding rod of the mechanism opens to the maximum 110 mm as the second layer with gear is rotated 77°.